Cobalt exposure was associated with the risk of hepatic steatosis and advanced liver fibrosis based on a cross-sectional study from NHANES - Ling Zhang; Shijie Ma; Rui Sun; Rui Xie; Peng Shen (Ecotoxicology and Environmental Safety)
Background: Although Emerging evidence suggests the association of environmental factors with hepatic steatosis and fibrosis, the relationship between Cobalt exposure and hepatic steatosis and fibrosis was not clear. Aim: Our study was aimed to explore the association between blood Cobalt level and hepatic steatosis and advanced liver fibrosis diagnosed by vibration controlled transient elastography (VCTE) in US adults. Methods: This study analyzed data from 3193 individuals participating in the 2017–2018 National Health and Nutrition Examination Surveys. Participants were classified into four groups according to the quartiles of blood cobalt concentration. Liver stiffness and fat content were assessed through vibration-controlled transient elastography (VCTE), including measurements of the controlled attenuation parameter (CAP). The association between blood cobalt levels and the prevalence of hepatic steatosis and advanced liver fibrosis was explored using logistic regression models and stratified subgroup analyses. Results: The CAP values showed a significant decline across increasing cobalt quartiles. Participants in the highest quartile had a 41 % lower risk of hepatic steatosis compared to those in the lowest quartile (odds ratio: 0.59, 95 % confidence interval: 0.46–0.76, p < 0.001). However, no significant association existed between blood Cobalt and advanced liver fibrosis. Subgroup analysis revealed that the relationship was consistent across age, gender and body mass index subgroups. Conclusions: This study showed that blood Cobalt level was negatively association with hepatic steatosis. This may be due to increased development from hepatic steatosis to advanced liver fibrosis upon Cobalt exposure.